Behavioral assessment of hippocampal function following dietary intervention - Klaus W. Lange; Ewelina Stollberg; Yukiko Nakamura; Joachim Hauser (Food Science and Human Wellness)
Pattern separation keeps items distinct in memory and is mediated by the hippocampus. A relationship between hippocampal function and diet quality has been suggested by findings in both humans and animals. In the present study, rats were fed over seven generations a diet containing increased amounts of sugar and saturated fatty acids, reduced levels of polyunsaturated fatty acids and an increased ratio of omega-6/omega-3 fatty acids (“Western” diet). Spatial pattern separation (or local discrimination) performance of these animals was compared with that of rats fed a standard diet. A separation-dependent difference between the standard and Western diet groups was found in the number of discriminations performed in the pattern separation task, with rats of the “Western” group performing fewer discriminations. The present results suggest that behavioral assessment of spatial pattern separation can detect effects of dietary interventions in rats and that pattern separation can be impaired by transgenerational administration of a “Western” diet. Future studies should determine which components of this diet induce the memory impairments related to the hippocampus. The translational relevance of these findings in regard to mental disorders such as dementia and depression needs to be investigated. Keywords: Memory, Hippocampus, Western diet, Fatty acids, Sugar